Redescription of Euastacus clydensis Riek, 1969 (Crustacea: Parastacidae), a valid species of spiny crayfish from southern New South Wales, Australia - van Der Wal, Cara; Ahyong, Shane T.; Lo, Nathan; Ho, Simon Y. W.; Mccormack, Robert B. (Zootaxa, 2022)
The Giant Sydney Crayfish (Euastacus spinifer (Heller, 1865)) was thought to have a wide range in New South Wales, Australia, spanning some 600 km north–south. A recent extensive molecular phylogenetic and population genomic analysis of E. spinifer across its geographical range revealed strong population structure corresponding to several major geographically correlated clades, the southernmost clade being the most genetically divergent and clearly a separate species. This southern clade corresponds to the junior synonym E. clydensis Riek, 1969 and is sister to the clade comprising the remaining populations of E. spinifer and Euastacus vesper. We formally remove E. clydensis from the synonymy of E. spinifer, increasing the recognised number of species of Euastacus to 54. Euastacus clydensis is redescribed based on type and other material, and is distinguished from E. spinifer by differences in abdominal spination and the form of the antennal scaphocerite. Euastacus clydensis has a restricted southern New South Wales range in the Shoalhaven and Jervis Bay–Clyde River catchments, from Moss Vale south to the vicinity of Clyde Mountain; much of the known range of E. clydensis was burnt in the 2019–2020 eastern Australian megafires.